THE INFLUENCE OF TEACHER CERTIFICATION BENEFITS AND DISCIPLINE TOWARD TEACHER PERFORMANCE IN ELEMENTARY SCHOOLS OF GORONTALO CITY - Imam Mashudi; Ningsih Amuja; Azis Rachman (Journal of Economic, Business, and Administration (JEBA), 2024)
The research aims at investigating the influence of teacher certification benefits towards teacher performance in elementary schools of Gorontalo City, the influence of discipline towards teacher performance in elementary schools of Gorontalo City, and the influence of teacher certification benefits and discipline teacher performance in elementary schools of Gorontalo City. This research is used a quantitative method with a descriptive approach, which reveals the influence of one variable on another. The population in this research are teachers receiving certification at the Elementary School of Gorontalo city, consisting of 523 people, while the sample was 130 people. Data is collected through the distribution of questionnaires. The findings reveal that the independent variables obtained information that the teacher's certification benefits (X1) have an influence toward performance (Y) of 0.2452 or 24.52% and discipline (X2) has an influence toward teacher performance (Y) of 0. 2072 or 20.72%. Simultaneously (X1) and (X2) have an influence toward(Y) of 45.24%. This research concludes that teacher certification benefits and discipline partially and simultaneously have a positive and significant influence on teacher performance in elementary schools in Gorontalo City is accepted. With the evidence that certification and discipline can improve teacher performance significantly, it is suggested (1) that the Gorontalo City Education Office is more intense in socializing and overseeing the implementation of teacher professional allowance criteria. (2) The school implements a teacher attendance system using fingerprints to obtain authentic data regarding attendance. (3) Teachers can improve the implementation of their duties as educators.